Das halbe Jahrhundert meiner Eltern - Kunze, Rolf-Ulrich 1968- (EUKLID Europäische Kultur und Ideengeschichte. Studien, 2015)
The titels alludes to the Dutch family history of Geert Mak ""De eeuw van mijn vader"" an exemplary history of Dutch society and mentalites. There are similarities to Walter Kempowskis historical narration ""Deutsche Chronik"" The double biographies of Rudi Kunze (1925 - 2001) and Gerda Kunze (1926 - 2010) are a unique, Hollywood-like movie plot and a characteristically German narration in the half century of extremes